2015
DOI: 10.18488/journal.107/2015.3.3/107.3.49.60
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Deepening on Economic Growth in Indian Perspective: ARDL Bound Testing Approach to Cointegration

Abstract: The present work is an attempt to investigate into the causal impact of financial deepening on economic growth in case of India. For analyzing the long term equilibrium relationship between the desired variables, we have employed Autoregressive Distributed Lag (ARDL) Bound testing approach. ARDL being a new approach is an improvement over the other traditional techniques of cointegration. Further, using the Granger Error Correction Model (ECM) technique we have tried to estimate the causal impact in the short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
3
11
2
Order By: Relevance
“…As for the variable ratio of total outstanding international debt securities have no effect on the long term, indicated by a value of the tstatistic is less than the value of the t-table with the real level of 5%. The results of this research, supports research Ghildiyal, Pokhriyal, and Mohan (2015) which states that in the long run, economic growth can be affected by the financial sector deepening.…”
Section: Source: Secondary Data Processedsupporting
confidence: 86%
“…As for the variable ratio of total outstanding international debt securities have no effect on the long term, indicated by a value of the tstatistic is less than the value of the t-table with the real level of 5%. The results of this research, supports research Ghildiyal, Pokhriyal, and Mohan (2015) which states that in the long run, economic growth can be affected by the financial sector deepening.…”
Section: Source: Secondary Data Processedsupporting
confidence: 86%
“…The ARDL bound test, which is the most appropriate method, used in such cases, was applied to data set. In contrast to the studies of Minier (2003) and Rioja and Valev (2004), all results, which are similarly to Shahbaz et al (2008), Goldsmith (1969), Levine and Zervos (1998), Boubakari and Jin (2010), Ghildiyal et al (2015), show that financial development and economic growth has positive correlation namely they are cointegrated and balanced in the long term.…”
Section: Conclusion and Discussioncontrasting
confidence: 50%
“…Seetanah (2008) documents evidence for the contribution of financial development to economic development in Mauritius. And, Ghildiyal et al (2015) found evidence for effect of financial development on economic growth in India. They recommend that to facilitate economic growth, the regulators need to provide easy credits and facilitate financial deepening.…”
Section: Discussion Of Findingsmentioning
confidence: 99%